The poetry of Arab women
1 online resource.
Keywords: This is a compilation of poetry written by Arabic women poets from pre-Islamic times to the end of the Abbasid caliphate and Andalusia, and offers translations of over 200 poets together with literary commentary on the poets and their poetry. This critical anthology presents the poems of more than 200 Arabic women poets active from the 600s through the 1400s CE. It marks the first appearance in English translation for many of these poems. The volume includes biographical information about the poets, as well as an analysis of the development of women's poetry in classical Arabic literature that places the women and the poems within their cultural context. The book fills a noticeable void in modern English-language scholarship on Arabic women, and has important implications for the fields of world and Arabic literature as well as gender and women's studies. The book will be a fascinating and vital text for students and researchers in the fields of Gender Studies and Middle Eastern studies, as well as scholars and students of translation studies, comparative literature, literary theory, gender studies, Arabic literature, and culture and classics.